Robin Hood [videorecording (Blu-Ray)] - Helgeland, Brian; Reiff, Ethan; Voris, Cyrus; Crowe, Russell, 1964-; Blanchett, Cate, 1969-; Addy, Mark, 1964-; Strong, Mark, 1963-; Sydow, Max von, 1929-2020; Hurt, William; Isaac, Oscar; Huston, Danny, 1962-; Atkins, Eileen; et al. (Universal, 2012)
In 13th century England, Robin and his band of marauders confront corruption in a local village and lead an uprising against the crown that will forever alter the balance of world power. And whether thief or hero, one man from humble beginnings will become an eternal symbol of freedom for his people.